Uveitis as a Confounding Factor in Retinal Nerve Fiber Layer Analysis Using Optical Coherence Tomography. (17th February 2022) - Yilmaz, Hayati; Koylu, Mehmet Talay; Çakır, Bağım Ayçin; Küçükevcilioğlu, Murat; Durukan, Ali Hakan; Bayer, Atilla; Mutlu, Fatih Mehmet
ABSTRACT: Purpose: To investigate the retinal nerve fiber layer thickness (RNFLT) in uveitic eyes and search for the associations with uveitis activity, etiology and location. Methods: The files of 76 patients with uveitis and 76 controls were scanned. Associations of RNFLT were analyzed using generalized linear models. Results: The RNFLT was significantly higher in patients with uveitis ( p < .001). Active uveitis patients had a thicker RNFL than the controls and the patients with quiescent uveitis ( p < .001). Anterior uveitis was associated with thinner RNFL in global and inferotemporal quadrant ( p = .011 and 0.013, respectively). Thickening of RNFL was associated with posterior uveitis and Behçet's disease in all quadrants ( p < .001) and idiopathic uveitis in the superonasal and nasal quadrants ( p = .001). Conclusion: Active uveitis, as well as posterior uveitis and Behcet's disease-associated uveitis, is a major confounding factor in RNFL analysis and therefore detection of glaucoma.